ZIMBABWES FORESTRY COMMISSION AND THE QUEST FOR SUSTAINABLE DEVELOPMENT - MAPIRA, Jemitias (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
This paper examines how some Zimbabwean government departments/organizations have been involved in the management of natural resources with a view to achieving sustainable development (SD) at local and national levels. This includes the Forestry Commission (FC) which dates back to the colonial era. Zimbabwes forest resources are governed by the Forest Act (Chapter 19:05) of 1996 (G.o.Z, 1996). The Act was proclaimed through an Act of parliament in 1949 and has been revised numerous times since its inception. Following the promulgation of the Act, a Forestry Commission was established in April 1954 in order to protect and conserve the countrys forest resources including indigenous and exotic species. During the 1990s Ngamo Safaris was established with a view to generating income for the FC. Since then, Ngamo Safaris has boosted the commissions coffers and brought financial stability to the organization. Unlike other government departments, ministries and NGOs, the FC is now self-reliant due to its income-generating projects. As such, it has become a model in the execution of its statutory mandate. The FC has been involved in such activities as tree planting, land reclamation and soil control. It has also been supplying villagers with tree seedlings with a view to promoting SD at local and national levels. However, in spite of this invaluable contribution, the FC is under-staffed at district, provincial and national levels, which undermines its regular operations.